Costa Rican technical and vocational education and training : development, challenges, and research perspectives - Rommel, Irina [Herausgeber]; Frommberger, Dietmar [Herausgeber]; Láscarez Smith, Daniel [Herausgeber] (Barbara Budrich, 2025)
"Technical and Vocational Education and Training (TVET) in Costa Rica has gained significant social, political, and economic relevance as a result of ongoing reforms, restructuring, and adaptation processes. The promotion and consolidation of the Costa Rican TVET system, as well as the establishment of a corresponding research discipline, have been central to international cooperation, particularly between Costa Rica and Germany. This volume provides a comprehensive insight into the Costa Rican TVET system and its related research by bringing together descriptive and empirical studies ranging from dual apprenticeship models, the linkage between the education and employment system to teaching-learning processes in the Costa Rican TVET system. The book is an important contribution to the academic discourse and the research needs for vocational education in Costa Rica." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 3.1 Berufsbildende Schulen; I 2.3.3 Lateinamerika; 370; Berufsbildung; Berufsbildungssystem; Berufsausbildung; Berufsbildungspolitik; Berufsbildende Schule; Lehrerbildung; Professionalisierung; Nationaler Qualifikationsrahmen; Arbeitsmarkt; Sozioökonomie; Costa Rica